Hematopoietic Stem Cell Transplantation Impact on Patients' Perceived Quality of Life: A Longitudinal Study - Pablo Ortolá-Alonso; Enric Santacatalina-Roig; Elena Chover-Sierra; Antoni Merelles-Tormo; María Luisa Ballestar-Tarín; Antonio Martínez-Sabater (MDPI AG, 2024)
Objective: The aim of this paper was to evaluate the quality of life of adult patients with onco-hematological disease treated with hematopoietic stem cell transplantation up to two years post-transplantation. Method: A quantitative, observational, longitudinal, and analytical study was conducted with 121 participants diagnosed with onco-hematological cancer who underwent hematopoietic stem cell transplantation between October 2017 and September 2019, with a 2-year post-transplantation follow-up, of whom only 39 completed the study. The Functional Assessment of Cancer Therapy-Bone Marrow Transplantation (FACT-BMT) questionnaire and its subscales, Functional Assessment of Cancer Therapy-General (FACT-BMT) and Functional Assessment of Cancer Therapy Trial Outcome Index (FACT-TOI), developed by the Functional Assessment of Chronic Illness Therapy (FACIT) and validated for Spain, were used to assess quality of life. Result: The average age for hematopoietic stem cell transplantation was 54 years, with a majority of male participants. The evaluation of quality of life showed a decrease at the time of hospital discharge, followed by a progressive improvement up to one year after the transplantation. There was a significant difference in the quality of life questionnaire scores between both sexes during all stages of the research, with higher scores in male participants. The length of hospital stay significantly affected patients' physical and functional well-being, and marital status was related to differences in the perception of quality of life. Conclusions: Despite the initial decrease in quality of life for patients undergoing hematopoietic stem cell transplantation, levels of quality of life similar to baseline are regained one year after the transplantation. Sociodemographic variables are related to how these patients perceive their quality of life. However, further studies with a larger sample size are needed for more precise results.